1987
DOI: 10.1172/jci112768
|View full text |Cite
|
Sign up to set email alerts
|

Circulating and tissue angiotensin systems.

Abstract: Angiotensin has many different actions, most of which relate, either directly or indirectly, to the regulation of blood pressure, fluid, and electrolyte homeostasis (1, 2). In addition to potent vasoconstrictor effects, actions ofangiotensin on vasculature include the stimulation ofprostaglandin release (3), the modulation of angiotensin receptor number (4), and the stimulation of angiogenesis (5). Angiotensin also has important actions on the central and peripheral nervous systems, the adrenal, kidney, intest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
167
0
10

Year Published

1991
1991
2010
2010

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 564 publications
(181 citation statements)
references
References 92 publications
2
167
0
10
Order By: Relevance
“…The renin-angiotensin system, which is one of the important factors underlying the mechanism of hypertension, is expressed locally in many tissues, including the heart [36, 37, 38], and this local renin-angiotensin system plays an important role in the cardiovascular disorders such as hypertrophy [37]and ventricular remodeling after myocardial infarction [38]. It has been shown that angiotensin II promotes the generation of superoxide radical by NADH/NADPH oxidase activation [39, 40], and free radical has been shown not only to cause the impairment of endothelium-dependent vasodilation [15]but also to mediate hypertrophic responses in myogenic cells [41].…”
Section: Discussionmentioning
confidence: 99%
“…The renin-angiotensin system, which is one of the important factors underlying the mechanism of hypertension, is expressed locally in many tissues, including the heart [36, 37, 38], and this local renin-angiotensin system plays an important role in the cardiovascular disorders such as hypertrophy [37]and ventricular remodeling after myocardial infarction [38]. It has been shown that angiotensin II promotes the generation of superoxide radical by NADH/NADPH oxidase activation [39, 40], and free radical has been shown not only to cause the impairment of endothelium-dependent vasodilation [15]but also to mediate hypertrophic responses in myogenic cells [41].…”
Section: Discussionmentioning
confidence: 99%
“…A direct effect of enalapril on the extracellular matrix protein synthesis is achieved by its ability to reduce the level of the protein kinase C agonist AngII by inhibiting the conversion of AngI to AngII by ACE. However, treatment with enalapril does not completely block the synthesis of AngII, since several enzymes other than ACE can convert AngI to AngII or can cleave angiotensinogen to release AngII directly [26]. …”
Section: Discussionmentioning
confidence: 99%
“…The rate-limiting step in the formation of angiotensin II (ANG II) is the proteolytic action of renin, which cleaves angiotensinogen (Aogen) to the intermediate angiotensin I (ANG I). ANG I is then converted to ANG II by angiotensin-converting enzyme (ACE) at the endothelial surface (2,3).…”
mentioning
confidence: 99%